Can dietary supplementation with highly purified fucoidan alter growth, digestive enzyme activity, serum biochemicals, immune-antioxidant responses, and related gene expressions in Nile tilapia (Oreochromis niloticus)? - Eman Y. Mohammady; Mohamed R. Soaudy; Mohamed A. Elashry; Ehab R. El-Haroun; Mohamed S. Hassaan (PLoS ONE, 2026)
The present study investigates the impact of dietary fucoidan supplementation on growth performance, intestinal tract morphology, endogenous digestive enzymes, hematological parameters, serum biochemical indices of Nile tilapia ( Oreochromis niloticus ), oxidative biomarkers, and related gene expressions. Fish weighing 2.54 ± 0.12 g had randomly assigned them into five groups of equal size (20 fish each aquarium), with three replicates per group. The fish were fed for 70 days with five experimental diets formulated: T1: Control (fucoidan 0 mg kg -1 ); T2: 0.5 mg kg -1 fucoidan; T3: fucoidan 1.0 mg kg -1 , T4: fucoidan 1.5 mg kg -1 and T5; fucoidan 2.0 mg kg -1 . At the end of the experiment, growth indices, feed utilization, digestive enzyme activity, intestinal histomorphometric, hematological indices, serum biochemical indices, and antioxidant enzyme activities were significantly (P < 0.05) increased in the groups fed diets supplemented by fucoidan, with the superiority of fish fed 2 mg kg -1 compared to the basal diet. Additionally, a control diet has the highest ALT and AST compared to other diets supplemented with different fucoidan levels. Fish fed either 1.5 mg kg -1 or 2.0 mg kg -1 fucoidan recorded the higher (P < 0.05) hematological parameters as WBCs, RBCs, neutrophils, lymphocytes, monocytes, and eosinophils. A diet supplemented with 2 mg kg -1 diet fucoidan displayed the highest gene expression of the inf-γ and il-1β , while the heat shock protein 70 ( hsp70 ) gene was down-regulated. Overall, our results highlight the efficacy of fucoidan in increasing growth performance, feed utilization, antioxidant enzyme activity, and gene expression. Therefore, it can be considered a promising feed additive for tilapia farming.